Pregnancy‐associated plasma protein A gene polymorphism in pregnant women with preeclampsia and intrauterine growth restriction. Issue 10 (28th September 2015) - Ozkan, Sultan; Sanhal, Cem Yasar; Yeniel, Ozgur; Arslan Ates, Esra; Ergenoglu, Mete; Bınbır, Birol; Onay, Huseyin; Ozkınay, Ferda; Sagol, Sermet
Abstract: Preeclampsia (PE) and intrauterine growth restriction (IUGR) are still among the most commonly researched titles in perinatology. To shed light on their etiology, new prevention and treatment strategies are the major targets of studies. In this study, we aimed to investigate the relation between gene polymorphism of one of the products of trophoblasts, pregnancy‐associated plasma protein A (PAPP‐A) and PE/IUGR.A total of 147 women (IUGR, n  = 61; PE, n  = 47; IUGR + PE, n  = 37; eclampsia, n  = 2) were compared with 103 controls with respect to the sequencing of exon 14 of the PAPP‐A gene to detect (rs7020782) polymorphism. Genotypes "AA" and "CC" were given in the event of A or C allele homozygosity and "AC" in A and C allele heterozygosity. Our findings revealed that the rate of AA, CC homozygotes, and AC heterozygotes did not differ between groups. Moreover, there was no difference in the distribution of PAPP‐A genotypes among the patients with IUGR, PE, IUGR + PE, or eclampsia. Finally, birth weight, rate of the presence of proteinuria, and total protein excretion on 24‐hour urine were similar in the subgroups of AA, AC, and CC genotypes in the study group. Our study demonstrated no association between PAPP‐A gene rs7020782 polymorphism and PE/IUGR.